Cultural Heritage, Religious Practice, and Contemporary Tourism in Nishiarai Daishi Temple - Wada, Akinori (Bali Tourism Journal, 2025)
Japanese Buddhist temples have long served as centers of both spiritual devotion and cultural interaction, shaping the social and religious fabric of their surrounding communities. This study examines Nishiarai Daishi Temple in Adachi Ward, Tokyo, One of the “Three Great Kant? Yakuyoke Monasteries” as a case study of how urban religious institutions in Japan balance sacred tradition with modern cultural and touristic engagement. Founded in 826 CE by the monk K?kai (K?b? Daishi), the temple’s origins in esoteric Shingon Buddhism and its reputation for protection against misfortune anchor its enduring religious significance. Over centuries, Nishiarai Daishi has evolved into both a pilgrimage destination and a communal hub, integrating architectural symbolism, folk practices, and seasonal aesthetics into its sacred landscape. The temple’s monthly ennichi festivals and the Osame no Daishi year-end celebration illustrate how ritual practice, local commerce, and social participation interweave to sustain community life and spiritual continuity. These events transform the temple precinct and surrounding streets into liminal spaces where sacred and secular experiences converge. In recent years, guided tours and intercultural programs have expanded Nishiarai Daishi’s role as a site of cultural tourism, allowing international visitors to participate in traditional rituals and experience intangible heritage firsthand. Through historical, ritual, and intercultural analysis, this study argues that Nishiarai Daishi exemplifies the adaptive resilience of Japanese Buddhist institutions. It demonstrates how temples mediate between devotion and display, preserving authenticity while embracing globalization, thereby functioning as living embodiments of Japan’s religious and cultural heritage.